The activity of azithromycin against Leishmania (Viannia) braziliensis and Leishmania (Leishmania) amazonensis in the golden hamster model A atividade da azitromicina contra a Leishmania (Viannia) braziliensis e a Leishmania (Leishmania) amazonensis no modelo golden hamster - Ángel Sinagra; Concepción Luna; David Abraham; Maria del Carmen Iannella; Adelina Riarte; Alejandro J. Krolewiecki (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
New therapeutic alternatives against leishmaniasis remain a priority. The activity of azithromycin against Leishmania (Leishmania) major has been previously demonstrated. Different responses among species of Leishmania make species-specific drug screening necessary. The activity of azithromycin against Leishmania (Viannia) braziliensis and Leishmania (Leishmania) amazonensis was evaluated in golden hamsters infected through footpad injections of metacyclic promastigotes, and compared with untreated controls and animals treated with meglumine antimoniate. Footpad thickness, lesion cultures and dissemination sites were analyzed. Treatment of golden hamsters with oral azithromycin at 450mg/kg had no activity against infections with Leishmania (Leishmania) amazonensis. For infections due to Leishmania (Viannia) braziliensis, azithromycin demonstrated significant activity relative to untreated controls, but inferior to meglumine antimoniate, for controlling lesion size. Neither drug was able to totally eliminate parasites from the lesions. It was concluded that azithromycin has activity against Leishmania (Viannia) braziliensis but not against Leishmania (Leishmania) amazonensis in this model. Novas alternativas terapêuticas contra a leishmaniose são ainda uma prioridade. A atividade da azitromicina contra a Leishmania (Leishmania) major foi anteriormente demonstrada. Diferentes respostas entre as espécies de Leishmania fazem com que um screening de drogas específicas para espécies seja necessário. A atividade da azitromicina contra a Leishmania (Viannia) braziliensis e a Leishmania (Leishmania) amazonensis foi avaliada em Golden hamsters infectados a través de injeções de promastigotas metacíclicas e comparando com controles sem tratamento e animais tratados com antimoniato de N-metil-glucamina. Foram analisadas a espessura da pata, a cultura das lesões e disseminação para órgãos internos. A azitromicina oral em dose de 450mg/kg não teve atividade contra a infecção por Leishmania ( Leishmania) amazonensis. Para ...